An extensive study of a diesel engine propelled with biodiesel blend of Karanja. (28th August 2020) - Panigrahi, Nabnit
An effort has been made to investigate the enhancing performance of a diesel engine using energy and exergy analysis technique propelled with diesel and KB20 (20% Karanja biodiesel by volume blended with 80% diesel by volume). The experiments were conducted per mole of fuel basis on a 3.5 kW single cylinder; water cooled engine with 1, 500 rpm. The energy analysis indicates that about 37.23% and 37.31% of input energy is converted into output work for diesel and KB20 fuel respectively. The combustion efficiency of KB20 was higher than that of diesel by 5.35%. Exergetic efficiency of diesel and KB20 was found to be 34.8%. Study indicates that KB20 biodiesel results coherence with the same energetic and exergetic performance as diesel fuel.